Optimizing strategy of computing off loading energy consumption based on Lagrangian method - Guangxue YUE; Youkang ZHU; Jiansheng LIU; Yasheng DAI; Zhenxu YOU; Hao XU (Dianxin kexue)
With the development of mobile network technology and the popularization and application of intelligent terminals,mobile edge computing has become an important application of cloud computing.Computing offloading strategy has become one of the key issues in mobile edge computing services.Targeting the total computing time of the mobile terminal and minimizing the energy consumption of the mobile terminal,the computation offloading resource allocation problem of the mobile terminal was modeled as a convex optimization problem,solved by the Lagrange multiplier method,and a threshold-based offloading was proposed.Simulation experiments show that the proposed offloading optimization strategy model can effectively balance the relationship between local computing and offloading,and provide guarantee for executing computation-intensive applications in mobile edge computing.